Kemampuan Mengidentifikasi Kelas Kata pada Novel “Mekkah Memoar Luka Seorang Tenaga Kerja Wanita (TKW) Karya Aguk Irawan MN” Siswa Kelas VIII SMP Unismuh Makassar - Hanana Muliana (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2023)
The main problem in this study is to see how far the ability of class VIII students of SMP Unismuh Makassar in determining the class of words in the text of the novel "Mekkah memoir the wound of a TKW" by Aguk Irawan MN. This study aims to describe the ability to identify word classes in the novel "Mecca memoirs the wound of a TKW" by Aguk Irawan MN Class VIII students of SMP UNISMUH Makassar. This type of research is quantitative descriptive research, the data obtained is in the form of answers which are the result of the questions contained in the test. The data obtained from the tests were processed using descriptive statistical techniques. The subjects in this study were students of class VIII which consisted of two classes, namely class VIII A which had 25 students and class VIII B which had 25 students. who obtained a score of 7 and above were (41 people (82%)), while students who obtained a score of 7 and below were (9 people (18%)). This has reached the criteria that become the standard of student ability, namely (80% or 40 students) who get a score of 7 and above. Keywords: